Piper betle shows antioxidant activities, inhibits MCF-7 cell proliferation and increases activities of catalase and superoxide dismutase - Abrahim Noor; Kanthimathi M S; Abdul-Aziz Azlina (BMC, 2012)
Abstract Background Breast cancer is the most common form of cancer and the focus on finding chemotherapeutic agents have recently shifted to natural products. Piper betle is a medicinal plant with various biological activities. However, not much data is available on the anti-cancer effects of P. betle on breast cancer. Due to the current interest in the potential effects of antioxidants from natural products in breast cancer treatment, we investigated the antioxidant activities of the leaves of P. betle and its inhibitory effect on the proliferation of the breast cancer cell line, MCF-7. Methods The leaves of P. betle were extracted with solvents of varying polarities (water, methanol, ethyl acetate and hexane) and their phenolic and flavonoid content were determined using colorimetric assays. Phenolic composition was characterized using HPLC. Antioxidant activities were measured using FRAP, DPPH, superoxide anion, nitric oxide and hyroxyl radical scavenging assays. Biological activities of the extracts were analysed using MTT assay and antioxidant enzyme (catalase, superoxide dismutase, glutathione peroxidase) assays in MCF-7 cells. Results Overall, the ethyl acetate extract showed the highest ferric reducing activity and radical scavenging activities against DPPH, superoxide anion and nitric oxide radicals. This extract also contained the highest phenolic content implying the potential contribution of phenolics towards the antioxidant activities. HPLC analyses revealed the presence of catechin, morin and quercetin in the leaves. The ethyl acetate extract also showed the highest inhibitory effect against the proliferation of MCF-7 cells (IC50=65 μg/ml). Treatment of MCF-7 cells with the plant extract increased activities of catalase and superoxide dismutase. Conclusions Ethyl acetate is the optimal solvent for the extraction of compounds with antioxidant and anti-proliferative activities. The increased activities of catalase and superoxide dismutase in the treated cells could alter the antioxidant defense system, potentially contributing towards the anti-proliferative effect. There is great potential for the ethyl acetate extract of P. betle leaf as a source of natural antioxidants and to be developed as therapeutics in cancer treatment.